Step
*
2
1
2
of Lemma
fun-path-fixedpoint
1. T : Type
2. f : T ⟶ T
3. u : T
4. u1 : T
5. v : T List
6. ∀[x,y,z:T].  (y = z ∈ T) supposing (((f y) = y ∈ T) and (y ∈ [u1 / v]) and z=f*(x) via [u1 / v])
7. x : T
8. y : T
9. z : T
10. z=f*(x) via [u; [u1 / v]]
11. (y ∈ [u1 / v])
12. (f y) = y ∈ T
⊢ y = z ∈ T
BY
{ ((FLemma `fun-path-cons` [-3] THEN Auto) THEN All Reduce THEN D -2 THEN Auto) }
1
1. T : Type
2. f : T ⟶ T
3. u : T
4. u1 : T
5. v : T List
6. ∀[x,y,z:T].  (y = z ∈ T) supposing (((f y) = y ∈ T) and (y ∈ [u1 / v]) and z=f*(x) via [u1 / v])
7. x : T
8. y : T
9. z : T
10. z=f*(x) via [u; [u1 / v]]
11. (y ∈ [u1 / v])
12. (f y) = y ∈ T
13. z = u ∈ T
14. x = u ∈ T supposing ¬0 < ||v|| + 1
15. u = (f u1) ∈ T
16. ¬(u = u1 ∈ T)
17. u1=f*(x) via [u1 / v]
⊢ y = z ∈ T
Latex:
Latex:
1.  T  :  Type
2.  f  :  T  {}\mrightarrow{}  T
3.  u  :  T
4.  u1  :  T
5.  v  :  T  List
6.  \mforall{}[x,y,z:T].    (y  =  z)  supposing  (((f  y)  =  y)  and  (y  \mmember{}  [u1  /  v])  and  z=f*(x)  via  [u1  /  v])
7.  x  :  T
8.  y  :  T
9.  z  :  T
10.  z=f*(x)  via  [u;  [u1  /  v]]
11.  (y  \mmember{}  [u1  /  v])
12.  (f  y)  =  y
\mvdash{}  y  =  z
By
Latex:
((FLemma  `fun-path-cons`  [-3]  THEN  Auto)  THEN  All  Reduce  THEN  D  -2  THEN  Auto)
Home
Index